Why did middle-aged and older people retire since the first COVID-19 lockdown? A qualitative study of participants from the Health and Employment After Fifty study - Stefania D'Angelo; Ilse Bloom; Georgia Ntani; Karen Walker-Bone (BMC, 2024)
Abstract Background Governments of Western countries need people to work to older ages, however the COVID-19 pandemic impacted the workforce by pushing older adults to retire. Socio-demographic factors that influence the decision to retire in the pre-pandemic period were, poor or good health, finances, marital status, and gender. The aim of this study was to explore aspects that contributed to the decision to retire among middle-aged and older people in England who retired during the COVID-19 pandemic. Methods In September 2022 semi-structured interviews were conducted with a sample of participants from the Health and Employment After Fifty (HEAF) study who retired since March 2020. Consenting participants were purposively selected to achieve a wide spread of characteristics deemed important in the retirement process. Telephone interviews were conducted, audio-recorded, transcribed and then thematically analysed. Results 24 interviews were conducted (10 men and 14 women, mean age 65 years). Six themes were identified: four of them were non-COVID-19 aspects while two can be interpreted as impact of COVID-19 on the workforce. Work-related factors were of major importance. A sense of appreciation and attachment in relation to their employer, and conversely high work demands and stress, as well as changes in work responsibilities and work practices since lockdown and/or perception of personal safety in the workplace during the pandemic influenced their retirement decision, as did physical and mental health issues. Another theme suggested that some participants felt they had reached the 'right' age and needed to spend more time with family. Having the financial capacity to retire was widely mentioned but was never the main factor. Conclusions The decision to retire during the pandemic was multi-factorial although changes to work during lockdown were of great importance. Post-pandemic, our findings suggest that there are modifiable aspects of work, including appreciation and fair pay and work conditions, that employers and policy makers could encourage to retain their older workers.